Analisis Tindak Tutur Ekspresif dalam Wacana Stand Up Seru Gusti Muhammad Abdurahman Bintang Mahaputra (Bintang Emon) di Kompas TV - Eri Dia, Eva; Tri Rusdiana, Imelya (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Expressive speech acts are a type of speech act in which the utterance expresses something that is meant by the speaker. This research uses a qualitative approach, by applying qualitative descriptive methods. The research objective to be achieved is to analyze expressive speech acts in the Stand Up Fun Bintang Emon discourse on Kompas TV. The data in this research is in the form of Stand up Fun Gusti Muhammad Abdurrahman Bintang Mahaputra (Bintang Emon) discourse on Kompas TV which is sourced from the YouTube page, in speech acts containing humor used by the speaker to express something that is intended to be conveyed to the speech partner (audience). In this research, there are six types of expressive speech acts. The types of expressive speech acts found in this research are: (1) praising speech acts, (2) criticizing speech acts, (3) complaining speech acts, (4) blaming speech acts, (5) insulting speech acts, and satirical speech acts.